Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Trigonometry

Asked by 16th September 2009, 1:31 PM
Answered by Expert
Answer:

We assume the following is the correct expression to be simplified.

[(1+sin2A)  +  (1-sin2A)] / [(1+sin2A) - (1-sin2A)]

Simplify using the following trignometric identities,

sin2 A + cos2 A = 1 and sin2A = 2sinAcosA

(1+sin2A) = (sin2 A + cos2 A + 2sinAcosA) = (sin A + cos A)2 = (sin A + cos A)

(1-sin2A) = (sin2 A + cos2 A - 2sinAcosA) = (sin A - cos A)2 = (sin A - cos A)

[(1+sin2A)  +  (1-sin2A)] / [(1+sin2A) - (1-sin2A)] =

 [(sin A + cos A) + (sin A - cos A)] / [(sin A + cos A) - (sin A - cos A)] =

= tan A

Regards,

Team,

TopperLearning.

Answered by Expert 16th September 2009, 2:59 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!